THERMODYNAMIC ANALYSIS OF THE GAS MEDIUM IN THE FORMATION OF DIFFUSION COATINGS USING COMPOSITE SATURATING CHARGES - Sereda, Borys; Khina, Borys; Kruglyak, Irina (Scientific Journal "Metallurgy", 2021)
Review of the main processes of formation of diffuse coatings doped with molybdenum,vanadium and tungsten. The basic features of the formation of diffusion layers during chemicalthermaltreatment are considered.: When the SHS is tested, the container is heated to temperaturesof 1173-1330 K. Within 1-2 hours, a diffusion coating is formed due to the saturation of thesurface of structural materials with atoms of saturating elements - Cr, Al, V, Ti, B, W, Mo. Assaturating elements, the defects of these elements and the chemical compounds of these elementswere used, and to determine the possibility of using specific substances, chemical reactionswere considered that can occur in the temperature range of diffusion saturation usingSOS. It should be noted that the metallothermal Reduced oxide, which is used in the synthesisof powder media for CHT, is very fast. When obtaining diffuse layers using the composition ofsaturating the medium, a gas phase is formed, containing spolo-I, I2, I3, H, H2, H3, Cl2, Cl3 withchemical elements. With an increase in temperature, an increase in the amount of halides isobserved. This confirms the possibility of transferring alloying elements for the formation of diffusioncoatings. Also, the amount of products in the gaseous phase increases and condensedproducts are released. It is characteristic that in the temperature range of 700-1500 K, the decompositionof reaction products occurs during CHT, which is confirmed by the production ofdecomposition substances and a sharp increase in the number of gas moles.